Karakteristik dan Identifikasi Senyawa Metabolit Skunder Teh Daun Sirsak (Anonna muricata Linn) - diningsih, ayus; Harahap, Cory Linda Futri; Harahap, Hasni Yaturramadhan (Jurnal Kesehatan Ilmiah Aufa Royhan, 2023)
Indonesia people generally consume boiled water of herbal plants to prevent or treat various diseases. To make it easier for people to consume herbal plants, one of which is in the form of tea. How to consume tea is very easy and practical, just by brewing it with hot water. The purpose of this research was to identify secondary metabolites contained in soursop leaf tea and to determine the characteristics of soursop leaf tea which included organoleptic tests, water content tests and ash content tests. This research is a true experiment in the laboratory. The results showed that the characteristics of soursop leaf tea (Annona muricata L) include organoleptic, soursop leaf tea has a brownish green color, powder form and has a soursop leaf aroma. The soursop leaves have water content and ash content respectively are 1.111% and 0.6444%. Soursop leaf tea positively contains secondary metabolites, namely flavonoids, alkaloids, tannins and saponins